Comparison of the Multinomial Naive Bayes Algorithm and Decision Tree with the Application of AdaBoost in Sentiment Analysis Reviews PeduliLindungi Application - Cecep Muhamad Sidik Ramdani; Andi Nur Rachman; Rizki Setiawan (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
One solution that the Indonesian government has implemented in controlling and tracking COVID-19 cases is using the PeduliLindungi application. User review data on the PeduliLindungi application is available on the Google Play Store, the data can be analyzed to determine the trend of public sentiment towards the PeduliLindungi application using sentiment analysis techniques. One of the methods used for sentiment analysis is machine learning, but in the machine learning method there is a problem, namely the relatively low level of accuracy. In this study, there are 2 machine learning algorithms that are used and compared, namely the Multinomial Naïve Bayes (MNB) and Decision Tree (DT) algorithms combined with the AdaBoost (AB) method to improve the accuracy of the PeduliLindungi application review data classification accuracy. In the experiment conducted, the tendency of public sentiment towards the PeduliLindungi application was 67% positive and 33% negative from a total of 8305 data. Multinomial Naïve Bayes before being combined with AdaBoost produces an average accuracy value of 83,7%, while Decision Tree produces an average accuracy value of 82,8%. After being combined, MNB+AB produces an average accuracy value of 88,8%, while the DT+AB method produces an average accuracy value of 84,1%. The use of AdaBoost can improve the accuracy of the Multinomial Naive Bayes algorithm and Decision Tree for the PeduliLindungi application review data classification process.